ANALISIS KELAYAKAN BERJALAN DAN FAKTOR YANG MEMENGARUHI MINAT BERJALAN KAKI DI JAKARTA - Kurniawati, Wahyuni; Ananta, Aris (Jurnal Kebijakan Ekonomi, 2020)
Walking is a main mode transportation for many of the world’s people, and connecting one mode transportation to other transportation. Pedestrian ways in Jakarta is not comfortable for pedestrian. Its mean, the sidewalk is not walkable, inadequate and pedestrian facilities are often dilapidated. Pedestrian facilities measured by walkability index. The aim of this research is to analyze demand walking based on demographic, sosio-economic, and walkability factors. Data collection techniques use observation, questionnaire survey, and short interview to pedestrian. This study use qualitative method with cross tabulation and quantitative method with logistic regression. Pedestrian facilities in Jalan Jenderal Sudirman has walkability index of 67,3 and Jalan Salemba Raya-Kramat Raya has an index walkability of 54,75. That’s mean those way in a sufficient condition. The result found that walkability factor is not related with demand for walking, and there is a good correlation of sosio-ecomomic and demographic factor. This indicate that the local governments in DKI Jakarta have to increasing the demand for walking, based on sosio-economic and demographic factors, not just focus on increasing the quality of pedestrian ways (walkability), even the sidewalk in a good condition, people in Jakarta is not necessarily willing to walk